1992
DOI: 10.1091/mbc.3.5.571
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human cyclin-dependent kinases in vitro.

Abstract: We have analyzed the activation of human cyclin-dependent kinases in a cell-free system. Human CDC2, cyclin-dependent kinase 2 (CDK2), cyclin A, and cyclin Bi were produced in insect cells by infection with recombinant baculoviruses. CDC2 or CDK2 monomers in lysates of infected cells could be activated by the addition of lysates containing cyclin A or Bi. CDC2 activation by cyclin B1, as well as CDK2 activation by cyclins A and Bi, was accompanied by the formation of high molecular weight complexes. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
180
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(191 citation statements)
references
References 43 publications
10
180
1
Order By: Relevance
“…Although the titer of cyclin varied slightly between batches, in all cases maximal inhibition was observed using <0.2 ,tM cyclin A. This concentration is lower than that of cyclin B used in a similar study (Thomas et al, 1992) and compares both with the concentration of cdc2 found in the cell (see Desai et al, 1992) and with levels of cyclin A required to induce meiosis (Roy et al, 1991) or activate cdc2 kinase (Clarke et al, 1992) in Xenopus. We also compared cyclin Aactivated cytosols with cytosols prepared from mitotic cells that contained elevated levels of cyclin B-cdc2 kinase.…”
Section: Inhibition Of Fusion Is Reversed By Addition Of Untreated Cymentioning
confidence: 62%
“…Although the titer of cyclin varied slightly between batches, in all cases maximal inhibition was observed using <0.2 ,tM cyclin A. This concentration is lower than that of cyclin B used in a similar study (Thomas et al, 1992) and compares both with the concentration of cdc2 found in the cell (see Desai et al, 1992) and with levels of cyclin A required to induce meiosis (Roy et al, 1991) or activate cdc2 kinase (Clarke et al, 1992) in Xenopus. We also compared cyclin Aactivated cytosols with cytosols prepared from mitotic cells that contained elevated levels of cyclin B-cdc2 kinase.…”
Section: Inhibition Of Fusion Is Reversed By Addition Of Untreated Cymentioning
confidence: 62%
“…Activation of CDK6 by KSHV-cyclin is unconventional and very strong. So far all cell cycle cdk/cyclin complexes examined have required phosphorylation of the activating threonine within the T-loop by CAK for full activity (Gould et al, 1991;Desai et al, 1992;Solomon et al, 1992; ConnellCrowley et al, 1993;Fisher and Morgan, 1994;Kato et al, 1994;Matsuoka et al, 1994;Aprelikova et al, 1995;Kaldis et al, 1996. The only exception is CDK7 and its orthologs, where binding of the assembly factor MAT1 to the CDK7/cyclin H complex can substitute for activating phosphorylation Kimmelman et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of an activating threonine (Thr-160 in CDK2 and Thr-177 in CDK6) by the cdk-activating kinase (CAK; reviewed by Kaldis, 1999) is accompanied by structural changes in the T-loop (also called the activation segment), allowing the phosphate group to interact with several other residues and thereby acting as an organizing center in the catalytic cleft (Russo et al, 1996b). Mutation of the acti- vating threonine to an unphosphorylatable amino acid prevents activation of vertebrate cdks (Desai et al, 1992;Solomon et al, 1992;Connell-Crowley et al, 1993;Kato et al, 1994;Matsuoka et al, 1994) and equivalent mutants are unable to support growth in yeast (Gould et al, 1991;Cismowski et al, 1995). Two very different CAKs have been identified.…”
mentioning
confidence: 99%
“…Soluble glutathione S-transferase (GST)-cyclin A/Cdk2, GST-cyclin E/Cdk2, GST-cyclin E/His6-Cdk3, and cyclin D/GST-Cdk4 complexes were produced in insect cells (High5, Invitrogen, San Diego, CA) and purified on glutathione-Sepharose (GSH-Sepharose, Pharmacia, Uppsala, Sweden) using established procedures (Desai et al, 1992;Matsushime et al, 1992;Harper et al, 1995). The sources of the baculovirus are as described (Harper et al, 1995) N-(2-hydroxyethyl)piperazine-N'-(2-ethanesulfonic acid), pH 7.6, 150 mM NaCl, 1 mM EDTA, 2.5 mM ethylene glycol-bis(3-aminoethyl ether)-N,N,N',N'-tetraacetic acid, 0.1 % Tween 20, 1 mM dithiothreitol, 5 mM NaF, 30 mM p-nitrophenyl phosphate, 25 mM (3-glycerol phosphate, 1 ,ug/ml leupeptin, 1 ,ug/ml antipain, and 1 mM PMSF] for Cdk4 complexes.…”
Section: Protein Purificationmentioning
confidence: 99%